Correlations between TDS and electrical conductivity for high-salinity formation brines characteristic of South Atlantic pre-salt basins - Lucas Rego Barros Rebello; Thauara Siepman; Santiago Drexler (Water SA, 2020)
Total dissolved solids (TDS) is an important property in the characterization of natural waters for diversified applications, such as in geochemistry and the petroleum industry. Under appropriate circumstances, the determination of this parameter through correlations with the electrical conductivity (EC) of aqueous systems yields considerable advantages over the gravimetric method. However, the development of empirical equations correlating TDS and EC is still required due to the physical-chemical complexity of charge transport in multicomponent natural waters. Most existing correlations were built considering systems in the lower or medium salinity range. In this context, this research aims to provide experimental correlations between TDS and EC in a broad concentration range for high salinity formation brines characteristic of the pre-salt reservoirs. It contributes to filling a gap in the literature for geochemical systems of this nature. Moreover, correlations were also obtained for a concentrated desulphated seawater and an aqueous sodium chloride solution in the same salinity range. For all aqueous solutions, the polynomial fittings of degree greater than one fit the experimental data better compared to both linear and exponential equations. In addition, the solutions with higher concentration of divalent ions had lower EC than the solutions dominated by monovalent ions with the same ionic strength. This evidences the effect of ion pairing on the EC, particularly in solutions of high ionic strength. Therefore, the use of a general correlation to represent solutions with dramatic variations in chemical composition carries substantial error, particularly in the high salinity range. Thus, a specific correlation must be developed to represent brines with similar composition.